Out for the count: some methodological questions in 'publications counting' literature - Losekoot, E; Verginis, CS; Wood, RC (Elsevier, 2001)
Comments on the use of 'publications counting', i.e. the number of items published by academics and their institutions, in making financial and tenure decisions, and criticizes the methods used in terms of the choice and relative status of the journals included in such counts, the timeframe for analysis relative to journal selection, and the arithmetic procedures employed, offering named examples from the field of hospitality and tourism. Contends that a fairer and more worthwhile benchmarking process is necessary, taking the example of the UK's research assessment exercise and advocating a more holistic approach than that currently pursued.
Keywords: Academic Staff; Publishing; Quantitative Techniques; Hospitality research; Journal status; Measurement of research output